MG-63 Cell Proliferation with Static or Dynamic Compressive Stimulation on an Auxetic PLGA Scaffold - Myeong Jin Kim; Hong Jin Choi; Jongman Cho; Jung Bok Lee; Hak-Joon Sung; Jeong Koo Kim (International Journal of Polymer Science)
The effect of dynamic compressive stimulation on MG-63 cell proliferation on an auxetic PLGA scaffold was investigated. The estimated Poisson ratio of the prepared auxetic scaffold specimens was approximately (−)0.07, while the Poisson ratio estimated for conventional scaffold specimens was (+)0.12 under 10% strain compression on average. Three stimulus groups were examined: control (no stimulation), static compression, and dynamic compression. In preparation for proliferation testing, cells were seeded at 2.2 × 105 cells/80 μL on each scaffold specimen. The average proliferation rates of the static and dynamic groups were higher than those of the control group: 13.4% and 25.5% higher at culture day 1, 34.7% and 56.2% at culture day 3, and 17.5% and 43.0% at culture day 5, respectively. The static and dynamic group results at culture day 5 were significantly different (p<0.01). Moreover, proliferation rate of the dynamic stimulation group was 1.22 times higher than that of the static group (p<0.01). Conclusively, proliferation of osteoblast-like cells was enhanced through compressive stimulation, but the enhancement was maximal with dynamic compressive stimulation of auxetic scaffolds.